Light-weight steel and aluminium structures : Fourth International Conference on Steel and Aluminium Structures, Espoo, Finland, 20-23 June 1999 /: Fourth International Conference on Steel and Aluminium Structures, Espoo, Finland, 20-23 June 1999. (1999) - Unknown
No abstract available